The relationship between physical activity and trait anxiety in college students: The mediating role of executive function - Dong, Zhiwei; Wang, Peng; Xin, Xin; Li, Shufan; Wang, Jing; Zhao, Jinlei; Wang, Xing (Frontiers in Human Neuroscience, 2022)
Objectives: Aimed to analyze the relationship between physical activity level, executive function, and trait anxiety. Methods: The International Physical Activity Questionnaire, State-Trait Anxiety Inventory, Stroop task, 1-back task, and More-odd shifting task were used to analyze 248 college students. Results: Trait anxiety were significantly correlated with shifting function (r=0.182, P=0.004) and inhibition function (r=0.163, P=0.010) and not with working memory (r=0.056, P=0.385). VPA was most highly correlated with inhibition function (Beta=-0.144, P=0.024) and working memory (Beta=-0.208, P=0.001), and LPA was most highly correlated with shifting function (Beta=-0.211, P=0.001). Physical activity had a 72.31% direct association with trait anxiety (B=-0.195), with 11.79% mediated by inhibition function (B=-0.023) and 15.90% by shifting function (B=-0.031). Conclusion: College students with trait anxiety suffer from impaired inhibition and shifting function. The facilitation effects of physical activity levels on executive function subcomponents were, in descending order, working memory, shifting function, and inhibition function, with VPA contributing most to the facilitation of working memory and inhibition function, and LPA contributing most to the promotion of shifting function. Physical activity promotes both inhibition and shifting functions, which in turn affect trait anxiety. VPA has a direct effect on trait anxiety, while the anxiolytic effect of MPA and LPA are mediated exclusively through executive functions, with the highest mediating effect of shifting function. It is recommended that college workers should motivate students with high trait anxiety to engage in more VPA and pay attention to changes in their inhibition and shifting functions.